Divergent roles of serum CXCL9 as a biomarker in ILD and COPD: a comparative study - Yin, Chengsheng; Kang, Xin; Zhang, Yuan; Song, Jiacui; Hasegawa, Takehiro; Yao, Ling; Hu, Yang; Li, Huiping (Frontiers in Pharmacology, 2026)
BackgroundThe chemokine CXCL9, induced by interferon-γ (IFN-γ), is a hallmark of type 1 (T1) inflammation. Its role in chronic respiratory diseases remains unclear, with conflicting evidence suggesting it may reflect steroid-responsive inflammation in interstitial lung disease (ILD) but correlate with worse function in chronic obstructive pulmonary disease (COPD).MethodsSerum levels of CXCL9, KL-6, SP-A, and CRP were measured in 83 ILD patients (with paired samples before and after treatment), 94 COPD patients, and 100 healthy controls (50 smokers and 50 non-smokers). Lung function and biomarker correlations were analyzed, and unsupervised cluster analysis was used to explore inflammatory phenotypes.ResultsCXCL9 levels were markedly elevated in both ILD (median: 57.4 pg/mL) and COPD (70.1 pg/mL) compared to healthy smokers (32.5 pg/mL) and non-smokers (37.0 pg/mL). In COPD, CXCL9 correlated with KL-6 (r = 0.459) and SP-A (r = 0.274), indicating neutrophilic inflammation and epithelial injury. In ILD, higher baseline CXCL9 levels predicted subsequent improvement in lung function and declined following treatment. Cluster analysis revealed divergent CXCL9 and KL-6 trajectories linked to disease outcomes, underscoring their value as dynamic, disease-specific biomarkers.ConclusionCXCL9 levels correlate with divergent roles in ILD and COPD. It may serve as a prognostic marker, identifying treatable inflammation in ILD and inflammatory burden in COPD.